Analysis of L-Shape Building with Lift Core at Different Locations And Its Torsional Effect - Adhikari, Sushil; Katuwal, Tek Bahadur; Thapa, Dipak; Lamichhane, Suraj; Adhikari, Dhurba (Technical Journal, 2020)
In L-shape building, lift core wall is an important element for strengthening the structure of high seismic zone area. Seismic zone V is considered for most of the buildings in Nepal, which will cause maximum base shear to the structure. This study focuses the use of lift core in five and ten-storey building to resist the seismic forces, and the effect of the lift core is also taken into consideration. Based on the location of the lift core, these building are further subdivided into different models; Lift at outer corner (model 1), lift at lower edge corner (model 2), lift at upper edge corner (model 3), lift at lower and upper edge corner (model 4), lift at inner corner (model 5), and lift at inner and outer corner (model 6). Equivalent static method and response spectrum analysis was used for the analysis. The structural responses were measured in terms of modal periods, displacement, drift ratio, and torsional irregularities. Results from this study indicate that building with lift core wall at inner and outer (model 6) and lift at lower and upper edge corner (model 4) shows the minimum drift ratio, torsional irregularities, displacement and natural time period which lies within permissible limit of torsional irregularities. Hence, it can be concluded that the location of the lift core affects the torsion of an L-shape plan asymmetric building. Designing two lift core at the inner and outer corner (model 6) and lower and upper edge corner (model 4) is found to be effective in reducing the torsion.